2018
DOI: 10.1371/journal.pone.0201890
|View full text |Cite
|
Sign up to set email alerts
|

A novel rare event approach to measure the randomness and concentration of road accidents

Abstract: BackgroundRoad accidents are one of the main causes of death around the world and yet, from a time-space perspective, they are a rare event. To help us prevent accidents, a metric to determine the level of concentration of road accidents in a city could aid us to determine whether most of the accidents are constrained in a small number of places (hence, the environment plays a leading role) or whether accidents are dispersed over a city as a whole (hence, the driver has the biggest influence).MethodsHere, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…On streets with large amounts of traffic (both higher speed and traffic volume), more accidents are expected [ 27 , 73 ]. Therefore, since traffic is concentrated in certain areas, and since environmental factors and some human errors occur more frequently in some areas than others, crashes are concentrated and form non-random hotspot patterns [ 40 ]. These include, for example, areas with a high density of pedestrians in the dark, or where there are “careless weekend drivers” [ 39 ].…”
Section: Detecting Spatio-temporal Patterns In Crime and Crashesmentioning
confidence: 99%
See 2 more Smart Citations
“…On streets with large amounts of traffic (both higher speed and traffic volume), more accidents are expected [ 27 , 73 ]. Therefore, since traffic is concentrated in certain areas, and since environmental factors and some human errors occur more frequently in some areas than others, crashes are concentrated and form non-random hotspot patterns [ 40 ]. These include, for example, areas with a high density of pedestrians in the dark, or where there are “careless weekend drivers” [ 39 ].…”
Section: Detecting Spatio-temporal Patterns In Crime and Crashesmentioning
confidence: 99%
“…Using existing legal or political definitions for neighbourhoods or districts often yields a more natural partition of a city. Yet, the dividing line between two distinct neighbourhoods is often a main avenue, and the edge between three of more neighbourhoods is often a main city node (such as a Metro station) which functions as an attractor node of crime and crashes [ 40 ]. This results in crucial gravity centres of the city being divided into distinct observation units.…”
Section: Constructing the Heartbeats Of Crime And Road Accidentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Smeed's 1949 pioneering work regarding statistical aspects of road traffic collisions [34], the precision and availability of both geographic and road safety data have improved considerably, enabling many other authors to expand the field [35][36][37][38][39][40][41][42]. Additionally, the more recent introduction of scaling models in the context of urban science [43] offers a new avenue for modelling road traffic collisions and understanding their behaviour.…”
Section: Urban Scaling Modelsmentioning
confidence: 99%
“…14 The presence of intersections, trees that obstruct vision while driving or walking, and pedestrian space occupied by informal businesses can increase the risk of crashes. 15,16,25 In this study, a greater number of accidents occurred on asphalt roads that were in good conditions and on roads that contained bicycle lanes. This is in line with previous studies that showed association of adverse infrastructure conditions, such as road surface conditions, street type and road width, lighting as well as location type with higher odds to RTA.…”
Section: Discussionmentioning
confidence: 70%